Applications of optical-feedback cavity-enhanced absorption spectroscopy - Bergin, A (2013)
This thesis presents two contrasting implementations of the optical-feedback cavity-enhanced absorption spectroscopy (OF-CEAS) technique. OF-CEAS com- bines passive optical-feedback locking of semiconductor lasers with cavity-enhanced absorption spectroscopy, and is well suited to sensitive detection of pressure- broadened trace gases. Chapters 1 and 2 set the work in this thesis in context, by describing the theory and discussing the motivations behind trace gas sensing by tuneable laser spectroscopy in the near- and mid-IR. Chapter 3 reviews the theory of OF-CEAS, prior to presenting the results of an experimental implementation based on a near-IR DFB diode laser setup following the traditional V-cavity methodology to spatially decouple the optical- feedback beam from the direct back reflection. The capabilities of the system are demonstrated by accurate determination of a self-broadened half-width at half- maximum of a CO 2 transition, and by detection of acetylene in a car exhaust sample. Chapter 4 describes the design and implementation of the linear cavity method- ology for QCL OF-CEAS, which is the significant contribution of this work. Successful OF-CEAS locking with the linear cavity is shown for two different DFB-QCLs, with close operating wavelengths (5.5 and 5.2 µm) but quite different operating powers and facet size. Chapter 5 presents quantitative spectroscopic results from the linear cavity OF-CEAS instrument, using both lasers. Spec- troscopy on mixes of N 2 O and NO returned sensitivities, quantified by the α min , of 2.7 × 10 −8 cm −1 in 1 s at 0.28 atm and 2.4 × 10 −8 cm −1 in 1 s at 0.19 atm respectively. Limited by etalon fringing on the baseline, the α min compared well with those obtained with V-cavity QCL OF-CEAS instruments. The temporal stability was investigated by Allan variance calculations and the best minimum detectable concentrations for the linear QCL OF-CEAS instrument were 32 ppm for N 2 O (35 s) and 5 ppb for NO (2 s). For NO, this detection limit compares favourably with other mid-IR QCL-based NO sensors, and is sufficient for mon- itoring NO in polluted urban environments. With the Maxion DFB-QCL, mon- itoring of NO in air outside the laboratory was attempted, and an air sample drying system benchmarked. Although this experiment proved unsuccessful, it was possible detect trace amounts of NO desorbing from the walls of the gas cell. Over the course of one hour the concentration rose from 3.8 ± 0.7 ppb to 28.4 ± 0.2 ppb, leading to a rate of desorption of 6.76 ± 0.01 × 10 −3 ppb s −1 . The sensitivity (α min ) of these spectra was 7.0 × 10 −9 cm −1 in 1 s, improved due to the higher mirror reflectivity at the lasing wavelength of the Maxion DFB-QCL, although still limited by etalon fringing.